Antike Judenfeindschaft in der hebräischen Bibel? - Spratte, Simon (Biblische Notizen, 2025)
The Hebrew book of Esther tells of the rescue of the Jewish people from the hands of their persecutor Haman, as well as from total annihilation. But what does the hostility towards the Jews described in this biblical book refer to? Its starting point is the figure of Haman in particular, who persuades the Persian king Ahasuerus to destroy the entire Jewish people due to an injury to his personal pride. His actions, the plan he devised and his reasoning can also be placed in the context of the whole history of hostility towards Jews and anti-Semitism and have influenced, for example, the later anti-Jewish and dismissive treatment of this biblical narrative. But could Haman’s plan and his argument before the king perhaps have been based on very specific experiences with anti-Jewish attitudes and events within the Jewish community of antiquity when the story was written? And can the figure of Haman therefore be understood as a kind of figuration of ancient forms of hostility towards Jews? This article aims to address this question by placing the exegetical analysis of the figuration of Haman in the Book of Esther in discourse with central anti-Jewish statements and events that could have been used and referred to in the genesis of the book.